MENINGKATKAN PROSES BELAJAR MENGAJAR DENGAN MENGGUNAKAN SISTEM E-LEARNING STUDI KASUS SMP NEGERI 24 PADANG - Yanti Yusman (Jurnal Teknologi Informasi dan Pendidikan, 2017)
There are some of students feel afraid to participate in learning, because there are some discussion or theme of learning is a problem that occurs in students of SMP Negeri 24 Padang Now this with Information and Communication Technology (ICT) learning process can be done through electronic media called e-learning. One way to use the right learning media so that students are more active to play a role in the learning process. As a medium that will be used by students and teachers then built Learning Management System with uses Analytic Network Process (ANP) method. Keywords: E-learning, ANP method